Disruption of the P2X7 purinoceptor gene abolishes chronic inflammatory and neuropathic pain. - Chessell, I; Hatcher, J; Bountra, C; Michel, A; Hughes, J; Green, P; Egerton, J; Murfin, M; Richardson, J; Peck, W; Grahames, C; Casula, M; et al. (2005)
The P2X(7) purinoceptor is a ligand-gated cation channel, expressed predominantly by cells of immune origin, with a unique phenotype which includes release of biologically active inflammatory cytokine, interleukin (IL)-1beta following activation, and unique ion channel biophysics observed only in this receptor family. Here we demonstrate that in mice lacking this receptor, inflammatory (in an adjuvant-induced model) and neuropathic (in a partial nerve ligation model) hypersensitivity is completely absent to both mechanical and thermal stimuli, whilst normal nociceptive processing is preserved. The knockout animals were unimpaired in their ability to produce mRNA for pro-IL-1beta, and cytometric analysis of paw and systemic cytokines from knockout and wild-type animals following adjuvant insult suggests a selective effect of the gene deletion on release of IL-1beta and IL-10, with systemic reductions in adjuvant-induced increases in IL-6 and MCP-1. In addition, we show that this receptor is upregulated in human dorsal root ganglia and injured nerves obtained from chronic neuropathic pain patients. We hypothesise that the P2X(7) receptor, via regulation of mature IL-1beta production, plays a common upstream transductional role in the development of pain of neuropathic and inflammatory origin. Drugs which block this target may have the potential to deliver broad-spectrum analgesia.